Influences of calcium silicate cement modified in glass ionomer cement on human pulp tissue using tooth culture model - Somudorn, Jirachaya; Sritanaudomchai, Hathaitip; Lapthanasupkul, Puangwan; Naruphontjirakul, Parichart; Pongprueksa, Pong (Mahidol Dental Journal, 2023)
Objectives: To study the influence of experimental bioactive material-modified in glass ionomer cements on dentin mineralization and pulpal morphology in the tooth culture model. Materials and Methods: Two experimental calcium silicate cement (Biodentine and MTA) modified in glass ionomer cement, glass ionomer cement (Fuji IXTM GP), and Biodentine were evaluated using a tooth culture model. The teeth were cultured for 28 days, then the histology procedure was performed and evaluated. The data was statistically analyzed using Fisher exact test analysis (α<0.05). Results: Biodentine showed significantly higher mineralization nodules at 28 days among others. Whereas two experimental calcium silicate cement (Biodentine and MTA) modified in glass ionomer cement did not show mineralization potential. Besides, all experimental materials showed pulpal biocompatibility and promoted pulpal inflammatory healing. Conclusions: Glass ionomer cement and the experimental calcium silicate cement modified glass ionomer cement were biocompatibility and promoted inflammation in the human pulp cell. However, the mineralization potential of these modified glass ionomer and glass ionomer cement was absent in this short period.